Cyclic Sieving Phenomenon in Non-Crossing Connected Graphs - Guo, Alan (The Electronic Journal of Combinatorics, 2011)
A non-crossing connected graph is a connected graph on vertices arranged in a circle such that its edges do not cross. The count for such graphs can be made naturally into a q-binomial generating function. We prove that this generating function exhibits the cyclic sieving phenomenon, as conjectured by S.-P. Eu.